ANALISIS PENGARUH PENGGUNAAN CELEBRITY ENDORSER SYAHRINI TERHADAP MINAT BELI MIE SEDAP DI DAERAH ISTIMEWA YOGYAKARTA - Norman Miradi Indra Kurniawan; Fitroh Adhilla (Universitas Ahmad Dahlan, 2017)
This study aims to analyze the effect of television advertising on buying interest in savory noodle products that are influenced by endorsement with Syahrini as a celebrity endorser. In this study the population used was general consumers who had seen delicious noodles ads through television media in the Special Region of Yogyakarta. This research is a quantitative research. Data collection using a questionnaire method (questionnaire) that has been tested for validity using CFA (Confirmatory Factor Analysis) and reliability testing using Crobach Alpha, while data analysis is performed using multiple linear regression analysis. The subjects of this study were general consumers who had seen advertisements of delicious Mie products on television media, the sampling technique used purposive sampling and incidental sampling methods, the number of samples used was 80 respondents. The results showed that (1) there was a significant influence between credibility on the interest in buying delicious noodle products, (2) there was a significant effect on the compatibility of buying interest in delicious noodle products. (3) There is a significant influence between the attractiveness of buying interest in delicious noodle products. There is a positive and significant influence between credibility, compatibility and attractiveness together to the interest in buying delicious noodle products.